Cost Model of Acquisition and Merger in Construction Industry - S. Harishwadha* (International Journal of Architectural Design and Planning, 2023)
Merger and Acquisition in India is at an all-time high with more buyers now than before; it has been accounting for 80% of closed deals in 2020–2021, up from 70% in 2017–2019. To determine the Merger and Acquisition of the company, this article explores the main factors in the Merger and Acquisition process. And also study the main framework of the Merger and Acquisition. And, also, the article discusses the critical success factors for the organization to accomplish its goal. This study will use a mixed method of both quantitative and qualitative data to explore the rate of investment, payback period profitability ratio that contribute to the positive outcomes of mergers and acquisitions. To make the correct decision about Merger and Acquisition of the firm, the client may share the sales through the right development. It is important to state the factors within the business principles associated with the cash flow and profitability of the business.
Keywords: Keywords: Cost model; acquisition process; hotel project; selecting criteria; stakeholders